Deepening the disciplinary cognition and constructing the theoretical system of socialist political economy with Chinese characteristics - Liu Can (China Political Economy (CPE), 2023)
Purpose - The socialist political economy with Chinese characteristics is a systematic economic discipline, which theoretically summarises the socialist economic system and the path of economic development with Chinese characteristics. It is a systematic economic theory of adapting Marxism to the Chinese context. The theoretical system construction for the discipline of socialist political economy with Chinese characteristics is currently a major task. Design/methodology/approach - From the perspective of disciplinary cognition, the theoretical system of the discipline of socialist political economy with Chinese characteristics includes the disciplinary attributes and connotations, theoretical basis, the origin of thoughts, major principles, logical starting point, main logic and problem-based study of major theoretical and practical issues. Findings - Developing the discipline and building the theoretical system of the socialist political economy with Chinese characteristics, several major principles should be adhered to, including building the socialist political economy with Chinese characteristics on the basis of historical materialism; building the theoretical paradigm of socialist political economy with Chinese characteristics around the analysis of production relations; adhering to the people-centred principle; taking common prosperity as the main logic of the socialist political economy with Chinese characteristics; studying the major theoretical and practical issues of building the socialism with Chinese characteristics in the new era based on problems; and reflecting the innovative development of the discipline in the textbook, The Socialist Political Economy with Chinese Characteristics. Originality/value - Disciplinary cognition involves the connotations, attributes, mission and development path of the discipline, which is related to how to construct the discipline system and is a significant part of the disciplinary construction.
Keywords: 330; Disciplinary cognition; Socialist political economy with Chinese characteristics; Theoretical system construction